BUDGETARY MECHANISMS FOR STIMULATING THE ISSUANCE OF GREEN BONDS IN THE FOREST SECTOR OF UKRAINE - Hrytsak, Oksana; Klym, Nadiia (Forestry Education and Science: Current Challenges and Development Prospects, 2026)
The paper examines the role of the budget system in stimulating the attraction of private capital for the greening of forestry. It is substantiated that one of the key barriers for entities in the woodworking industry is the high transaction costs associated with the preparation and verification of "green" projects in accordance with international standards. A conceptual approach to the cluster issuance of green bonds through mechanisms of state targeted expenditures is outlined. The uniqueness of the approach lies in the possibility of budgetary co-financing of external verification procedures (SPO) through the targeted allocation of environmental tax revenues. This allows reducing barriers to entry into the capital market for SMEs and increasing the transparency of the use of funds in accordance with ESG principles.